Preserving Cultural Heritage in Aceh: Legal Frameworks and Community Initiatives in Gampong Pande - Hasan Basri M. Nur; Abdullah, Munawiah; Husda, Husaini; Mukhtar, Marduati; Armia, Muhammad Siddiq (Lentera Hukum, 2025)
This paper examines the efforts to preserve cultural heritage in Aceh, Indonesia, with a specific focus on Gampong Pande, one of the oldest and most historically significant areas in Banda Aceh, Indonesia. As a site of early Islamic civilization in the region, Gampong Pande holds valuable tangible and intangible cultural assets, including ancient tombs, artifacts, oral traditions, and Islamic scholarly heritage. However, these cultural resources face increasing threats due to urban development, environmental degradation, and a lack of comprehensive preservation strategies. The study explores how the legal frameworks at the national and regional levels, particularly the implementation of Qanun (Acehnese regional regulations), are employed to protect and manage cultural heritage. These legal instruments provide a foundation for cultural governance, yet their effectiveness often depends on enforcement mechanisms and institutional coordination. In parallel, this study emphasizes the critical role of local communities in cultural preservation. It highlights how the residents of Gampong Pande have initiated grassroots movements to protect historical sites, resist commercial encroachment, and revive cultural practices. These initiatives demonstrate the importance of community participation, local wisdom, and intergenerational knowledge transfer in heritage conservation. This research underscores the need for a more integrated and participatory approach that combines top-down legal policies with bottom-up community action. It calls for stronger collaboration among government agencies, civil society, academic institutions, and local leaders to ensure the sustainable preservation of cultural heritage in Aceh. In conclusion, the preservation of Gampong Pande’s heritage means protecting physical structures and maintaining the region’s historical identity, spiritual legacy, and cultural continuity amid ongoing modernization and change. Keywords: Cultural Heritage, Aceh, Gampong Pande.